IMPLEMENTASI DATA MINING DENGAN ALGORITMA APRIORI UNTUK MEMPREDIKSI TINGKAT KELULUSAN MAHASISWA - Irham Kurnawan; Fitri Marisa; Purnomo Purnomo (Universitas Merdeka Malang, 2018)
Informatics Engineering Program University of Widyagama Malang has many volume of student databases. When properly excavated, so can known patterns or knowledge for a decision-making. Data that can be explored is the understanding of information about graduation students. This research to predict the passing rate of students with more efficient time, which can be known before the student graduated so that can be evaluated in their studies, especially in Informatics Engineering University of Widyagama. In this case using association methods and Apriori algorithm. This method calculates the support value that is the supporting value of an item with big golden rule 60% of the data of course grade. The results of this study to help universities improving the quality of education and help in knowing the information about the graduation rate of students based on the value of the subjects and achievement index obtained by students in Informatics Engineering course University of Widyagama MalangDOI: https://doi.org/10.26905/jtmi.v4i1.1894